Embeddedness and policy attitudes an exploratory study involving a social network of mayors in Bohol, Philippines - Lapitan, Aileen V.; Palis, Florencia G. (2016)
This paper is an exploration of the different measures of embeddedness within social network of mayors in Bohol, Philippines. Inquiry was perched on the prospects of elucidating policy transfer mechanism through the social network approach (SNA). SNA was applied in the characterization of embeddedness traits of the mayors. Results of the survey indicate higher incidence of policy attitude similarly between a mayor and his immediate (ego) network peers compared to the similarity with peers in the broad network. The paper an intriguing picture of local policy transfer dynamics from a network prespective whereby interactions beyond local jurisdictional boundaries can be examined for possible influence on policy attitude similaritied. It submits recommendations for further application of SNA in local policy process research and practice.
Keywords: Social media; Policy transfer; Mayors